Legal Protection of Danantara Directors in the Implementation of the Business Judgment Rule: A Comparative of Indonesia, Malaysia, and Singapore - Kristoforus Mamahit; Richard C. Adam (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the Business Judgment Rule provides legal protection to directors in making business decisions as long as they act in good faith, with due care, and without conflicts of interest; however, in reality in Indonesia, such protection remains suboptimal due to the dualism between corporate law and state finance law, which creates legal uncertainty and the potential criminalization of business decisions. This study aims to analyze the legal protection of directors in the application of the Business Judgment Rule and to compare its implementation in Malaysia and Singapore in order to formulate a model that ensures legal certainty and utility. The research employs a library research method with a qualitative approach and a normative juridical methodology, using statutory, conceptual, and comparative approaches. The findings indicate that Indonesia has not consistently implemented the Business Judgment Rule, in contrast to Singapore’s more stable application and Malaysia’s hybrid model. Therefore, a reconstruction through an Integrated Business Judgment Rule Protection model is necessary, emphasizing legal harmonization, the distinction between business risk and state loss, and institutional strengthening.